Assessment of knowledge regarding anaemia and its preventive measures among lactating mothers of North Gujarat region, India - Nimbalkar, Pankajkumar B.; Joshi, Maulik D.; Thakor, Nilesh; Bhatt, Avirat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Anaemia in pregnancy and lactation period has detrimental effects on maternal and child health. Objective of this study was to assess knowledge of lactating mothers regarding anaemia and its preventive measures before and after educational intervention. Methods: The interventional study conducted in purposively selected lactating mothers attending the outpatient department of obstetrics and gynecology. Hospital ethical committee permission was obtained. After taking informed consent 100 lactating mothers were selected by systemic random sampling methods. Knowledge of lactating mothers regarding anaemia and its preventive measures was assessed by pre-designed, pre-tested and semi structured questionnaire. Health education for 30 minutes was given to selected lactating mothers. Knowledge of pregnant women for the same was assessed after health education. Thus, collected data was analyzed using Epi info 7. Results: Awareness among lactating mothers regarding causes, signs and symptoms of anemia and dietary sources of iron was 41%, 26% and 5% respectively which was significantly increased to 73%, 56% and 42% respectively after health education. Awareness among lactating mothers regarding factors which inhibit and increase iron absorption was 31% and 22% respectively which was significantly increased to 80% and 65% respectively after health education. Out of 100 lactating mothers only 24% were aware regarding treatment of anemia. Conclusions: Lack of awareness among lactating mothers regarding anemia and its preventive measure should be addressed by health education during hospital visits.